Successful treatment of disfiguring facial scar using surgery combined with superficial radiotherapy: a case report with literature review - Zong, Yong-xia; Song, Yinghua; Deng, Shuang; Zhang, Liang; Li, Ze (Frontiers in Oncology, 2025)
IntroductionFacial scars are generally disfiguring and can cause both physiological and psychological trauma. Currently, there is a lack of effective treatment options for facial scars. In recent years, local superficial radiation therapy has emerged as a clinically proven treatment to effectively prevent scar recurrence after surgery.Case presentationOur patient was a 41-year-old male with a disfiguring facial scar caused by extensive burns. The patient underwent surgery for his facial scar; however, the scar recurred after surgery. Then, the patient underwent superficial radiotherapy, after which the patient’s facial scar flattened gradually, and his face was restored to normal. No significant adverse reactions were observed after 1 year of follow-up.ConclusionThe results indicate that superficial radiotherapy may promote the atrophy of hypertrophic scar tissue and can restore the normal appearance of the skin by reshaping the wound repair process.